Epidermal expression of human TRPM8, but not of TRPA1 ion channels, is associated with sensory responses to local skin cooling. Issue 12 (December 2019) - Weyer-Menkhoff, Iris; Pinter, Andreas; Schlierbach, Hannah; Schänzer, Anne; Lötsch, Jörn
Abstract : Abstract: Human cold perception and nociception play an important role in persisting pain. However, species differences in the target temperature of thermosensitive ion channels expressed in peripheral nerve endings have fueled discussions about the mechanism of cold nociception in humans. Most frequently implicated thermosensors are members of the transient receptor potential (TRP) ion channel family TRPM8 and TRPA1. Regularly observed, distinct cold pain phenotype groups suggested the existence of interindividually differing molecular bases. In 28 subjects displaying either high or medium sensitivity to local cooling of the skin, the density at epidermal nerve fibers of TRPM8, but not that of TRPA1 expression, correlated significantly with the cold pain threshold. Moreover, reproducible grouping of the subjects, based on high or medium sensitivity to cooling, was reflected in an analogous grouping based on high or low TRPM8 expression at epidermal nerve fibers. The distribution of TRPM8 expression in epidermal nerve fibers provided an explanation for the previously observed (bi)modal distribution of human cold pain thresholds which was reproduced in this study. In the light of current controversies on the role of human TRPA1 ion channels in cold pain perception, the present observations demonstrating a lack of association of TRPA1 channel expression with cold sensitivity–related measures reinforce doubts about involvement of this channel in cold pain in humans. Since TRP inhibitors targeting TRPM8 and TRPA1 are currently entering clinical phases of drug development, the existence of known species differences, in particular in the function of TRPA1, emphasizes the increasing importance of new methods to directly approach the roles of TRPs in humans. Abstract : Supplemental Digital Content is Available in the Text.The distribution of TRPM8 but not TRPA1 expression in epidermal nerve fibers provides an explanation of the (bi)modal distribution of human cold pain thresholds.